Dukungan Organisasional sebagai Moderator Hubungan Motivasi Intrinsik dan Kepribadian Individu dengan Kreativitas: Studi pada Dosen Perguruan Tinggi di Surabaya - Wulani, Fenika (Jurnal Widya Manajemen & Akuntansi, 2004)
The purposes of this research are to examine effect of organizational support as moderating variable on the relationship between intrinsic motivation and creativity, and that effect on the relationship between individual personality and creativity. The sample was lecturer that working in university in Surabaya. Hierarchical regression analysis show that organizational support wasn't gives effect on the relationship between intrinsic motivation and creativity. Organizational support was given effect on the relationship between individual personality and creativity.